Application of Technology Acceptance Model (TAM) in Telemedicine Application During Covid-19 Pandemic - Galuh Puspitarani Sudaryono, Noverinda; Fadhiil, Mahmud; Syarifah, Syarifah; Rinawati Simanjuntak, Evi (Journal of World Science, 2023)
The COVID-19 pandemic hit the whole world, including Indonesia, forcing people to limit all activities outside their homes, including treatment activities to hospitals. This study aims to examine the application of the technology acceptance model (TAM) to telemedicine applications during the COVID-19 pandemic. The proposed research model is formulated from the extended technology acceptance model theory with empirical testing using data obtained from telemedicine user surveys. This study analyzed two additional external factors: privacy concerns and trust. Data is processed using SmartPLS software. A total of 406 telemedicine users participated in this study with male, n=206; 51%, female, n=200; 49%. Research respondents habitually used telemedicine applications during the COVID-19 pandemic that hit Indonesia. Among these respondents, 94.7% reported using telemedicine services during the COVID-19 pandemic. The most widely used telemedicine application, with a total of 59.7% of respondents, chose Halodoc. The external variable privacy concern does not affect the perceived usefulness of telemedicine used. However, trust and perceived usefulness are associated with a positive significance in telemedicine used during the COVID-19 pandemic in Indonesia. Privacy concerns have a limited impact on the perception of expediency but influence the ease of use of telemedicine apps. On the other hand, trust plays a vital role in shaping telemedicine's perceived usefulness and ease of use during the COVID-19 pandemic, as telemedicine has become indispensable for accessing healthcare services.